The syntax of Cape Verdean Creole : the Sotavento varieties - Baptista, Marlyse (Linguistik aktuell ;, 2002)
This book offers an in-depth treatment of a variety of morpho-syntactic issues in Cape Verdean Creole (CVC) both from a descriptive and theoretical perspective. The investigated topics include the determiner system, Tense, Mood, Aspect markers and pronominal paradigms. The study of TMA markers reveals morpho-syntactic configurations with interesting ramifications for syntactic theory and parametric variation. This book targets creolists, theoretical linguists, and the Cape Verdean community. Given the diversified targeted audience, the descriptive chapters are purposefully kept separate from their theoretical counterparts, presenting issues that are later revisited in the Minimalist framework. The data used in this study are primarily drawn from 83 transcribed interviews from a pool of 187 speakers. The interviews were collected during fieldwork conducted in 1997, 2000 and 2001 in the Cape Verdean Sotavento (leeward) islands representing the more basilectal varieties of the creole. As all natural languages, CVC displays syntactic similarities and differences with other creoles and noncreoles. Hence, in the spirit of comparative syntax, this volume compares CVC to other creoles like Guinea-Bissau Creole and to noncreoles like Portuguese, French, Icelandic and Italian dialects.